Edukasi Metode Kontrasepsi Jangka Panjang (MKJP) Bagi PUS Kel. Samata Kec. Somba Opu Kab. Gowa - Nia Karuniawati; Andi Masnilawati; Sitti Hadriyanti Hamang (Window of Community Dedication Journal, 2024)
According to the effectiveness of the duration of contraceptive methods, there are two types, namely long-term contraceptive methods (MKJP) and non-MKJP. Long-term contraceptive methods are contraceptives that can be used for a long period of time, more than two years, are effective and efficient for the purpose of spacing births for more than 3 years or ending pregnancies in couples who no longer want to have more children. The types of methods included in this group are stable contraceptive methods (male and female), implants and intrauterine devices (IUD). Based on Indonesian family profile data in 2018, the type of contraceptive chosen by MKJP family planning participants is still very low, namely 17.8% of the total number of modern family planning participants and 82.19% use non-MKJP family planning. One factor that influences contraceptive use is knowledge. Limited knowledge will influence the mother's choice of contraceptive method. Correct knowledge about family planning programs, including various types of contraception, will increase community participation in family planning programs, therefore it is necessary toprovide education to increase PUS knowledge regarding long-term contraceptive methods (PUS). Partner Problems: Lack of knowledge regarding long-term contraceptive methods even though the majority of PUS choose to use MKJP. The results of the activities that have been carried out show that PUS knowledge has changed, where the average pre-test result is 81% with sufficient knowledge and after being given education regarding long-term contraceptivemethods (MKJP), the results have changed to 95% with good knowledge